1995
DOI: 10.1093/clinchem/41.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Analytical artifacts in hematocrit measurements by whole-blood chemistry analyzers

Abstract: Compact analyzers suited to near-patient testing estimate hematocrit by measuring the conductivity of undiluted blood. We evaluated the accuracy of hematocrit determination of one such analyzer (Instrumentation Laboratory BGE analyzer) against an automated cell counter (EPC) and packed cell volume (PCV) microhematocrit. When specimens (n = 34) from outpatient and ward patients were analyzed with all three methods, the BGE analyzer correlated well with both EPC and PCV hematocrit determinations (BGE = 1.00 PCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…One of the most frequently used methods for measuring Hb in ICU or during surgical interventions is via the blood‐gas analysers, based on either conductivity or spectrophotometry. Although conductivity‐based POCT devices provide accurate Hct results in normal subjects (Stott et al , ), results can be erroneously low or high during haemodilution or the alteration of plasma proteins, electrolytes or triglycerides. Discrepancies of up to 20 g/l for Hb and 4% for Hct have been reported (Hopfer et al , ).…”
Section: Haemoglobin Poct In Hospital Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequently used methods for measuring Hb in ICU or during surgical interventions is via the blood‐gas analysers, based on either conductivity or spectrophotometry. Although conductivity‐based POCT devices provide accurate Hct results in normal subjects (Stott et al , ), results can be erroneously low or high during haemodilution or the alteration of plasma proteins, electrolytes or triglycerides. Discrepancies of up to 20 g/l for Hb and 4% for Hct have been reported (Hopfer et al , ).…”
Section: Haemoglobin Poct In Hospital Settingsmentioning
confidence: 99%
“…Discrepancies of up to 20 g/l for Hb and 4% for Hct have been reported (Hopfer et al , ). As these dynamic changes are likely to occur during surgery or ICU, the conductivity‐based POCT results should be interpreted with caution in these circumstances (McMahon & Carpenter, ; Stott et al , ; McNulty et al , ; Hopfer et al , ; Stadlbauer et al , ). A downward bias has been demonstrated when the Hct is below 30% (al‐Odeh et al , ).…”
Section: Haemoglobin Poct In Hospital Settingsmentioning
confidence: 99%
“…They reported a bias of only 2.78%, which was surprisingly lower than all other POC devices they evaluated, even with the hematocrit result range varying widely from 24 to 45% [10]. These authors did not have an explanation for why the bias was so much lower for the EPOC® device's hemoglobin in their study, especially since it was not consistent with the results of the other POC devices they had tested which utilized similar technology or prior literature that demonstrated that other POC devices using conductometric hemoglobin measurements were not that accurate in similar patient populations [10,[17][18][19].…”
Section: Discussionmentioning
confidence: 88%
“…This phenomenon is explained by the overestimation of true volume of erythrocytes due to the entrapment of plasma in the cellular layer. 79 Also the contribution of leukocytes and platelets for the total volume of erythrocytes can be considered, however, their volume in practice is neglected. 79 These results suggest that intravascular hemolysis was negligible and cannot be attributed to PVA vascular grafts as proved before at in vitro hemolysis testing that considered this biomaterial as non-hemolytic (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…79 Also the contribution of leukocytes and platelets for the total volume of erythrocytes can be considered, however, their volume in practice is neglected. 79 These results suggest that intravascular hemolysis was negligible and cannot be attributed to PVA vascular grafts as proved before at in vitro hemolysis testing that considered this biomaterial as non-hemolytic (data not shown). In fact in vitro hemolysis testing correlates well with the in vivo findings and most of altered erythrocyte morphology observed by implantation of vascular grafts was related to altered blood flow rather than by incompatible blood-material interactions.…”
Section: Discussionmentioning
confidence: 99%